2012
DOI: 10.3233/jad-2012-121381
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Aloe Polymannose Multinutrient Complex on Cognitive and Immune Functioning in Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a leading killer of Americans, imparts a significant toll on the quality of life of the patient and primary caregiver, and results in inordinate costs in an already overburdened medical system. Prior studies on cholinesterase inhibitors among AD patients have shown minimal amelioration of disease symptoms and/or restoration of lost cognitive functioning. The effect of improved nutrition, particularly with dietary supplements, on cognitive functioning may offer an alternative strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“…Participants tolerated the APMC supplement with few, temporary adverse reactions. The present results showed improvements in both preliminary clinical and physiological outcomes for a decrease that otherwise has no standard ameliorative remedy [62] .…”
Section: Preliminary Clinical Studymentioning
confidence: 54%
“…Participants tolerated the APMC supplement with few, temporary adverse reactions. The present results showed improvements in both preliminary clinical and physiological outcomes for a decrease that otherwise has no standard ameliorative remedy [62] .…”
Section: Preliminary Clinical Studymentioning
confidence: 54%
“…Presumably, the wider array of nutrients in the fish, such as its vitamins and trace elements, produced its superior results. We previously showed improvements in cognitive and immune functioning and inflammation in persons with Alzheimer's disease in response to a dietary supplement containing multiple nutrients, such as polysaccharides, antioxidants, and omega-3 fatty acids, among others [19]. We also found that the combination of gingko biloba and choline produced modest improvements in cognitive functioning and inflammation in a sample of healthy elderly adults [20].…”
Section: Introductionmentioning
confidence: 68%
“…Participants tolerated the APMC supplement with few, temporary adverse reactions. The results showed improvements in both clinical and physiological outcomes for disease that otherwise has no standard ameliorative remedy [73] .…”
Section: Neuro-stimulation and Insulin-sensitivity Of Aloe Veramentioning
confidence: 85%